Insurgências urbanas e direito à cidade na perspectiva de ativistas em Belo Horizonte - Vitória Régia Izaú (2017)
This thesis aimed to understand the intrinsic meanings of the struggle for the right to the city by activists in the city of Belo Horizonte. The current scenario in Brazil of various manifestations and demands by the populations residing in the urban peripheries, with acute and fierce questions to the State, has shown the need to analyze more and more the senses of the actions of these subjects. In this perspective, the analysis construct also sought to identify the participation of the subjects in the demonstrations that took place in June 2013 in the city, a historical moment that marks the nonconformity with the constant prevalence of economic and political interests to the detriment of social issues. The thesis has as central question the perception of the concept Right to the city and the proposals of the activists for a new conception of the city, more focused on their interests. It starts from the idea that the city is plural, diverse, that activists are also constructors of the material and immaterial city. The right to the city, in addition to a well-intentioned rhetoric, is fundamentally about existing, resisting, building, sharing, and for this, it is perceived the need for the peripheral population to be recognized as a city people, heard and respected in their pressing needs for mobility, work and training. The particularity of the study about the city in this analysis, is the extent to which we become readers, but also constructors of educational action and the citizen scene in the urban environment, understanding the senses that the city has for the subjects researcher in their own voice. The perspective of a project of another city are important signs that point to the broad need for greater knowledge about the sociabilities and meanings of lifestyles, especially for residents in the urban peripheries as subjects that explicit and experience segregation and violation of their rights. It is a qualitative study that counted on 10 narrative interviews, articulating the individual and collective conceptions of the subjects. Urban insurgencies are bodies, voices, ideals, and stories of resistance on the move to a more just, democratic and anti-racist, anti-macho and anti-capitalist society.